2008
DOI: 10.1211/jpp.60.3.0012
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Schisandra chinensis extract and its biologically-active constituents across Caco-2 cell monolayers — an in-vitro model of intestinal transport

Abstract: We have determined the intestinal transport of Schisandra chinensis extract and its lignans (gomisin A, gomisin N and schisandrin C) in the Caco-2 cell monolayer model. The transport across monolayers was examined for 2 h in absorptive and secretory directions. Quantitation of lignans was performed by HPLC. Out of the three lignans, gomisin A exhibited bi-directional transport, with P(app) values in the range of 25-29 x 10(-6) cm s(-1), indicating a passive diffusion. Gomisin N, mixture and Schisandra extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…The active ingredients in the alkaloid fraction of the decoction were identified and the water extract of schisandra fruit significantly inhibited rat CYP3A in vitro in a concentration-dependent manner, with an IC 50 of 123 µg/mL, which was similar to the value for inhibition of erythromycin N-demethylation in human liver microsomes (13). It has also been found that several constituents, gomisins B, C, G and N and γ-shizandrin, isolated from Schisandra sphenanthera can interact with CYP3A4 (13)(14)(15)(16).…”
Section: In Nt Tr Ro Od Du Uc Ct Ti Io On Nmentioning
confidence: 73%
“…The active ingredients in the alkaloid fraction of the decoction were identified and the water extract of schisandra fruit significantly inhibited rat CYP3A in vitro in a concentration-dependent manner, with an IC 50 of 123 µg/mL, which was similar to the value for inhibition of erythromycin N-demethylation in human liver microsomes (13). It has also been found that several constituents, gomisins B, C, G and N and γ-shizandrin, isolated from Schisandra sphenanthera can interact with CYP3A4 (13)(14)(15)(16).…”
Section: In Nt Tr Ro Od Du Uc Ct Ti Io On Nmentioning
confidence: 73%
“…Because of toxicity, the application of bufalin in measuring CYP3A4 activity in living cells is limited. Additionally, GA exhibits high membrane permeability with a passive diffusion manner [45], which provides the possibility of performing a cell-based assay. The CYP3A4 mRNA level was significantly upregulated in the rifampin-treated group, while the CYP3A5 mRNA level was not remarkably induced, possibly because CYP3A5 is far less susceptible to induction than CYP3A4 [46].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, we suggested that the clinically beneficial drug interaction of S. sphenanthera is likely a result of its inhibition of CYP3A4. Consistent with this hypothesis, a number of recent in vitro studies also suggest that the components isolated from S. chinensis or S. sphenanthera are capable of altering CYP activity [10][11][12]. …”
mentioning
confidence: 68%
“…Based on these results, we suggested that the clinically beneficial drug interaction of S. sphenanthera is likely a result of its inhibition of CYP3A4. Consistent with this hypothesis, a number of recent in vitro studies also suggest that the components isolated from S. chinensis or S. sphenanthera are capable of altering CYP activity [10][11][12]. In recent years, several CYP3A4 substrates have been proposed in the literature as metabolic probes to evaluate the catalytic activity of CYP3A4 in vivo and in vitro, including testosterone, MDZ and 7-benzyloxy-4-trifluoromethylcoumarin.…”
mentioning
confidence: 77%